The effects of additives on anti-wear properties of lubricating grease formulated from waste engine oil - Nurul Waheeda, Abdu Rahman; Mohd Aizudin, Abd Aziz (Egyptian Petroleum Research Institute, 2022)
The goal of this study was to study the anti-wear properties of grease formulated from waste engine oil (WEO) when additives are added. There were two types of grease formulated namely sodium and fumed silica (FS) greases. The greases were formulated using a weight percentage ratio with and without the addition of additives before the attributes of consistency, FTIR (Fourier transform infrared spectroscopy), and anti-wear analysis were conducted. Results showed that the addition of additives did not affect the properties of the formulated grease except for that of sodium grease as demonstrated by the FTIR result. Sodium grease produced a spectrum with a peak in the region < 600 cm−1 when analyzed using FTIR. The corrosiveness of the grease toward the copper strip was also low, as determined by class 1 corrosiveness. The addition of additives resulted in no improvement in the anti-wear properties of the grease as the coefficient of friction (COF) was low for the grease without additives than for the grease with additives. However, the addition of additives can reduce the wear scar diameter of the greases. Based on the findings of this investigation, it was found that the addition of additives did not alter the properties of the greases or improve the anti-wear properties of the greases except for the wear scar diameter.